The Rights of Customary Law Communities to Resources: The Relationship of Coexistence of State Law and Customary Law - Jayantiari, I Gusti Agung Mas Rwa; Rumiartha, I Nyoman Prabu Buana; Arjawa, I Gst Pt Bagus Suka; Laksana, I Gusti Ngurah Dharma; Indradewi, Anak Agung Sagung Ngurah (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
This research aims to determine and analyze the relationship between state law and customary law regarding the rights of customary law communities to natural resources. The application of state law and customary law is a fact related to the lives of customary law communities and their areas of life which are inseparable from natural resources. Apart from constitutional recognition as stipulated in 18 B paragraph (2) of the 1945 Constitution of the Republic of Indonesia, various laws and regulations in the natural resources sector also provide space for regulation of customary law communities based on policies that tend to be centralized. The research method used is normative legal research with statutory, conceptual and factual approaches with qualitative prescriptive analysis. The research results found that customary law as a guideline for managing natural resources by customary law communities does not yet fully exist because the recognition of customary law communities is partial. In the perspective of John Griffith’s theory of legal pluralism, the relationship between state law and customary law is categorized as weak legal pluralism because of the dominant right to control the state through state law. Integration of coexistence between customary law and state law can only be realized if there is a law that specifically regulates customary law communities so that it is no longer determined based on the sectoral ego of various laws that regulate natural resources.